2021
DOI: 10.4103/ccd.ccd_720_20
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gingival recession coverage by Er,Cr:YSGG laser root biomodification

Abstract: Gingival recession predisposes to functional and aesthetic concerns, for which many surgical procedures are available. Among these, till now subepithelial connective graft is considered as the gold standard technique for its higher predictability of achieving recession coverage. However, it does not heal by new attachment, thus many techniques to promote new attachment such as root biomodification are done. This case enumerates the use of Er, Cr: YSGG laser for root biomodification to treat a wide and deep gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Moreover, Turer et al ( 2020 ) used i‐PRF with CTG for the treatment of deep GR defects and they observed complete RC at 88% of the sites treated with CAF + CTG + i‐PRF and 80% of the sites treated with CAF + CTG. The current study had a similar result to Damante et al ( 2019 ), Murugan et al ( 2021 ), and Turer et al ( 2020 ), where a significant reduction was observed in RD. Although recession decreased in both groups, better coverage was observed in the FGG + i‐PRF group.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, Turer et al ( 2020 ) used i‐PRF with CTG for the treatment of deep GR defects and they observed complete RC at 88% of the sites treated with CAF + CTG + i‐PRF and 80% of the sites treated with CAF + CTG. The current study had a similar result to Damante et al ( 2019 ), Murugan et al ( 2021 ), and Turer et al ( 2020 ), where a significant reduction was observed in RD. Although recession decreased in both groups, better coverage was observed in the FGG + i‐PRF group.…”
Section: Discussionsupporting
confidence: 91%
“…In the study of Damante et al (2019), they used citric acid/tetracycline gel (CAT) and antimicrobial photodynamic therapy for RSB with CTG treatment, where they observed that both the CAT group and PDT group have higher RC (82.1% and 81.6%, respectively) in comparison with scaling and root planning group (57.7%) (Karayürek et al, 2019). Furthermore, Murugan et al (2021), andTurer et al (2020), where a significant reduction was observed in RD. Although recession decreased in both groups, better coverage was observed in the FGG + i-PRF group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations